Gold transport in aqueous versus organic fluids: Experimental data and natural observations for describing ore-forming systems - Crede, Lars-Steffen (Curtin University, 2018)
The common association of carbonaceous matter (CM) with ore deposits is poorly understood. To understand the Au ore + CM association the ability of liquid hydrocarbons to act as an ore fluid was determined experimentally, and via analysis and textural observations of CMrich samples from the AuHg McLaughlin deposit in California, USA. Experimental data suggest that, below ~200 °C hydrocarbon (Au) ore fluids may be more effective transporters of Au than aqueous ore fluids.